Shadow Theater Games and projects - Bailey, Vanessa; Robson, Denny (Gloucester Press New York, 1991)
A step-by-step approach to shadow theater, from hand shadows to shadows with accessories made from simple materials.
Includes index
Keywords: Shadow shows -- Juvenile literature; Shadow puppets -- Juvenile literature; Puppet making -- Juvenile literature